The use of aerial photography in the search for Long Barrows of the Funnel Beaker culture in the area of southern Kuyavia - Papiernik, Piotr; Brzejszczak, Rafał (Acta Archaeologica Lodziensia, 2018)
Between August 2014 and July 2017, the Konrad Jażdżewski Foundation of Archaeological Research conducted a series of aerial surveys, which aimed to re-examine the location of the Kuyavian long barrows, known from archival sources. Over a dozen of the barrows were explored by professor Konrad Jażdżewski in the 1930s. The other ones are now completely levelled. The aerial survey was carried out on the area of the following villages: Obałki, Leśniczówka (currently Arciszewo), Lubomin, Śmieły, and Łania (c.f W. Chmielewski 1952). In the summer of 2015, a survey over the valley of the Zgłowiączka river was conducted. It encompassed the villages of Dęby Janiszewskie and Janiszewo, which according to descriptions, contained numerous Kuyavian long barrows. The aerial surveys in search of Kuyavian long barrows are still in progress. Until now, almost 130 flights have been made, which resulted in nearly 7500 photographs taken. On the basis of the obtained results, it seems that the applied method is very effective. Thanks to the flights over Izbica Kujawska and Lubraniec, it was possible to locate 17 long barrows cemeteries at Dęby Janiszewskie, Janiszewo, Leśniczówka, Lubomin, Obałki, Śmieły and Łania. The results obtained are relevant from the point of view of conservation works. As the long barrows are situated on arable land, they are gradually being destroyed and threatened with obliteration. Translated by Agata & Bogusław Maryniak